Bacterial Nanotubes as Intercellular Linkages in Marine Assemblages - Patel, Nirav; Yamada, Yosuke; Azam, Farooq (Frontiers in Marine Science, 2021)
Several types of bacterial appendages, e.g., pili and fimbriae, are known for their role in promoting interactions and aggregation with particles and bacteria in the ocean. First discovered in Bacillus subtilis and Escherichia coli, but novel to marine bacteria, bacterial nanotubes are hollow tubular structures connecting cell pairs that allow for the internal transport of cytoplasmic metabolites across the connecting structure. While the significance of nanotubes in exchange of cytoplasmic content has been established in non-marine bacteria, their occurrence and potential ecological significance in marine bacteria has not been reported. Using multiple high-resolution microscopy methods (atomic force microscopy, scanning and transmission electron microscopy), we have determined that marine bacteria isolates and natural assemblages from nearshore upper ocean waters can express bacterial nanotubes. In marine isolates Pseudoalteromonas sp. TW7 and Alteromonas sp. ALTSIO, individual bacterial nanotubes measured 50–160 nm in width and extended 100–600 nm between connected cells. The spatial coupling of different cells via nanotube connections can last for at least 90 minutes, extending the duration of interaction events between marine bacteria within natural assemblages. The nanomechanical properties of bacterial nanotubes vary in adhesion and dissipation properties, which has potential implication for structural and functional variability of these structures in their ability to stick to surfaces and respond to mechanical forces. Nanotube frequency is very low among cells in enriched natural assemblages, where nanotubes form very short, intimate connections, less than 200 nm, between certain neighboring cells. Bacterial nanotubes can form the structural basis for a bacterial ensemble and function as a conduit for cytoplasmic exchange between members for multicellular coordination and expression. The structural measurements and nanomechanical analyses in this study also extends knowledge about the physical properties of bacterial nanotubes and their consequences for marine microenvironments. The discovery of nanotube expression in marine bacteria has significant potential implications regarding intimate bacterial interactions in spatially-correlated marine microbial communities.